Dynamics of thymol dietary supplementation in quail (Coturnix japonica): Dataset on thymol bioavailability, egg yolk fatty acids profile and performance traits - Maria E. Fernandez; Jackelyn M. Kembro; Maria L. Ballesteros; Jorge M. Caliva; Raul H. Marin; Maria C. Labaque (Data in Brief, 2019)
Dietary supplementation with thymol (2-isopropyl-5-methylphenol) has been proposed as a strategy to improve modern intensive poultry production. Moreover, its antioxidant properties and potential beneficial influence on lipid metabolism have fostered current research focusing on enhancing nutritional quality of meat and egg products. In general, studies have focused on the overall effects of dietary supplementation once the supplementation protocol has finished and using only one potential dose, without actually measuring bioactive compounds' concentration in the diet supplied or target tissues. Herein, we provide a unique dataset of the dynamics of thymol bioavailability and biological action, optimal dosage and duration of supplementation needed to achieve meaningful effects, as well as persistence of induced changes after chronic supplement withdrawal. Specifically, during a month-long supplementation period, 5 sampling points were evaluated separated by at least 1 week. Then, a last sampling point was studied after a 3-week withdrawal period. Three increasing doses of dietary thymol were used, and approximately 80 variables assessed. The measured variables were associated with free thymol concentration in feed, egg yolk and droppings, feed and egg yolk fatty acids profile (saturated, unsaturated, and polyunsaturated fatty acids), performance traits (body weight, feed intake, egg laying rate, egg physical characteristics), general welfare quality assessment (plumage state) and liver histopathology. The data can provide insights on the link between the dynamics of free thymol concentration and the changes in fatty acids profile in quail egg yolk, both during chronic thymol dietary supplementation and after supplement withdrawal. The comprehensive approach used herein for studying thymol supplementation outcome could help understanding the scope of its effects on a whole organism level. Keywords: Natural products, Feed additives, PUFA, MUFA, SFA, Liver histopathology, Healthy, Eggs, Poultry nutrition